Rethinking the ecological drivers of hominin evolution. (September 2021) - Faith, J. Tyler; Du, Andrew; Behrensmeyer, Anna K.; Davies, Benjamin; Patterson, David B.; Rowan, John; Wood, Bernard
Abstract : A central goal of paleoanthropology is understanding the role of ecological change in hominin evolution. Over the past several decades researchers have expanded the hominin fossil record and assembled detailed late Cenozoic paleoclimatic, paleoenvironmental, and paleoecological archives. However, effective use of these data is precluded by the limitations of pattern-matching strategies for inferring causal relationships between ecological and evolutionary change. We examine several obstacles that have hindered progress, and highlight recent research that is addressing them by (i) confronting an incomplete fossil record, (ii) contending with datasets spanning varied spatiotemporal scales, and (iii) using theoretical frameworks to build stronger inferences. Expanding on this work promises to transform challenges into opportunities and set the stage for a new phase of paleoanthropological research. Highlights: Research aiming to understand the role of ecological change in hominin evolution has fueled the generation of paleoclimatic and paleoenvironmental records across Africa. Limitations of conventional methods for inferring ecology–evolution relationships mean that more data have not always led to a deeper understanding of hominin evolution. We outline several challenges that have hindered progress, and highlight how recent research is addressing them. This research is confronting the limitations of the fossil record, contending with proxy records spanning a range of spatiotemporal scales, and providing a stronger inferential approach to hypothesis testing. Addressing the obstacles that have hindered progress will enable a more robust understanding of the relationships between ecological change and hominin evolution.